Calcium Silicate Board as Wall-facade. (2017) - Kristanto, Luciana; Sugiharto, Handoko; Agus, S.W. Dwi; Pratama, S. Aditya
Abstract: Wall as spatial partition and facade of a building gives impact not only for building aesthetic, but especially for the occupant's convenience. In the preference of wall material, especially for high rise apartments, hotels or offices, its mass/m2 and its noise reduction become an important criteria that must be considered by the building owner and architect in order to give a more lightweight construction and a quieter interior for occupant's convenience and privacy. In this paper, lightweight material that has been investigated is calcium silicate board, as an alternative to brick as a common wall material. The findings of this research, by flexural strength test in normal condition, are generally categorized in class 2 and 3. By soak-dry test as durability test for outside uses, there are no cracks found in all samples and the flexural strength decreases but less than 30% so that it meets the SNI 7705:2011 standard. By warm water test, this material cannot withstand against temperature at 60 degree centigrade or higher. By heat and rain test, this material can withstand the heat and rain conditions. By noise reduction as sound isolating enclosure, this material is unable to perform as a noise barrier.